(untitled) (Journal of International Crisis and Risk Communication Research, 2023)
In 2017, the Nicholson School of Communication (NSC) took the initial steps to launch the Journal of International Crisis and Risk Communication Research because for more than 15 years, crisis and risk scholars had called for a dedicated journal focused on the growing interest in crisis and risk research. With a new NSC Director in place and an established International Crisis and Risk Communication Conference drawing scholars to the University of Central Florida since 2011, the decision was made for NSC to become the journal’s publisher and funds were earmarked to make its publication a reality.